Modelling maintenance costs of buildings under warranty - Ginevičius, Romualdas; Andruškevičius, Algirdas (Technological and Economic Development of Economy, 2004)
An essential link in building construction is maintenance under warranty. It is hardly possible to predict now how the cost and time of building construction will affect maintenance costs and alternations during this period. A correlation regression analysis has shown that the higher is the cost of the project, the higher the expenses, while the longer the time of the contract, the lower the costs. The total effect of the size and time of the project on the maintenance costs is positive implying that the higher they are, the greater are the expenses. Expenses under warranty spread parabolically, i. e. they are the highest at the beginning and at the end of the considered period and the lowest in the middle of the time. The cost and duration of a building contract has no direct impact on the distribution of building maintenance costs during the period under warranty. Article in Lithuanian. Pastatų garantinės priežiūros išlaidų modeliavimas First Published Online: 21 Oct 2010